Exploring the Digital Innovation Landscape in the Livestock Sector in India – A rapid assessment - Banerjee, Rupsha R.; Singh, Kanika; Annaiah, Akshatha; Dhulipala, Ram; Kennady, Vijayalakshmy (International Livestock Research Institute, 2024)
The livestock sector in India significantly contributes to the rural economy and national GDP but remains underutilized despite its potential. Use and promotion of digital technology provides real time opportunity to mainstream the sector, enhance livestock productivity and resilience across different livestock systems. The study identifies gaps in service delivery, including barriers such as high costs, technological complexity, limited use cases, and distrust, which hinder widespread adoption. Recommendations include strengthening extension systems for last-mile delivery, co-creating demand driven solutions with communities and generating evidence through focused case studies to attract investments.